2009
DOI: 10.1042/bj20090687
|View full text |Cite
|
Sign up to set email alerts
|

Specific role of phosphoinositide 3-kinase p110α in the regulation of phagocytosis and pinocytosis in macrophages

Abstract: PI3K (phosphoinositide 3-kinase) alpha has been implicated in phagocytosis and fluid-phase pinocytosis in macrophages. The subtype-specific role of PI3K in these processes is poorly understood. To elucidate this issue, we made Raw 264.7 cells (a mouse leukaemic monocyte-macrophage cell line) deficient in each of the class-I PI3K catalytic subunits: p110alpha, p110beta, p110delta and p110gamma. Among these cells, only the p110alpha-deficient cells exhibited lower phagocytosis of opsonized and non-opsonized zymo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 47 publications
1
36
0
Order By: Relevance
“…Murine macrophage uptake of LDL by fl uid-phase pinocytosis is consistent with reports showing that genetic knockout of the scavenger receptors SRA and/or CD36, which mediate uptake of oxidized LDL, does not affect lipid accumulation and foam-cell formation in murine atherosclerotic plaques ( 41,42 Although we did not examine other PI3K isoforms in this study, it was previously reported that the murine macrophage cell line RAW264.7 takes up FITC-labeled dextran in a PI3K ␣ -dependent manner ( 34 ). The authors attributed PI3K ␣ -mediated uptake by RAW264.7 cells to fl uid-phase pinocytosis, even though uptake of the fl uidphase pinocytosis tracer Lucifer Yellow was shown to occur independently of PI3K ␣ .…”
Section: Discussionsupporting
confidence: 77%
“…Murine macrophage uptake of LDL by fl uid-phase pinocytosis is consistent with reports showing that genetic knockout of the scavenger receptors SRA and/or CD36, which mediate uptake of oxidized LDL, does not affect lipid accumulation and foam-cell formation in murine atherosclerotic plaques ( 41,42 Although we did not examine other PI3K isoforms in this study, it was previously reported that the murine macrophage cell line RAW264.7 takes up FITC-labeled dextran in a PI3K ␣ -dependent manner ( 34 ). The authors attributed PI3K ␣ -mediated uptake by RAW264.7 cells to fl uid-phase pinocytosis, even though uptake of the fl uidphase pinocytosis tracer Lucifer Yellow was shown to occur independently of PI3K ␣ .…”
Section: Discussionsupporting
confidence: 77%
“…It is likely, however, that some degree of compensation occurs between p110 isoforms and that different isoforms may be utilized depending on the stimuli and cell type. Based on short hairpin RNA (shRNA) knockdown, a role for p110␣ has also been found in the RAW264.7 macrophage cell line downstream of the Fc␥ receptor (68). Despite this, it has been reported by the same group that knockdown of p110␤ reduces LPS-induced Akt phosphorylation, while knockdown of p110␣ or knockout of p110␥ has no effect (56), suggesting that isoform specificity varies with respect to the receptor that is activated.…”
Section: Discussionmentioning
confidence: 96%
“…Similarly, treatment with the TRPV1 antagonist SB366791 reduced phagocytosis when incubated with WT adherent macrophages. Also, the gene expression of PI3Ka and b, involved in ROS production, phagolysosome formation, and phagocytosis (31,32), was considerably reduced in CLP TRPV1KO mice. This provides evidence that TRPV1 can influence the response to infection by facilitating macrophage antibactericide function, thus acting via a protective mechanism associated with release of NO and ROS.…”
Section: Discussionmentioning
confidence: 99%
“…PI3Ka and b are involved in phagolysosome formation and also ROS production by macrophages (31,32). CLP TRPV1KO peritoneal cells express less PI3Ka and b when compared with CLP WT cells (Fig.…”
Section: Trpv1 Deletion Affects Phagocytosis Via the Nk 1 Receptor Fomentioning
confidence: 99%